Procalcitonin (PCT) levels for ruling-out bacterial coinfection in ICU patients with influenza: A CHAID decision-tree analysis. Issue 2 (February 2016) - Rodríguez, Alejandro H.; Avilés-Jurado, Francesc X.; Díaz, Emili; Schuetz, Philipp; Trefler, Sandra I.; Solé-Violán, Jordi; Cordero, Lourdes; Vidaur, Loreto; Estella, Ángel; Pozo Laderas, Juan C.; Socias, Lorenzo; Vergara, Juan C.; et al.
Summary: Objectives: To define which variables upon ICU admission could be related to the presence of coinfection using CHAID (Chi-squared Automatic Interaction Detection) analysis. Methods: A secondary analysis from a prospective, multicentre, observational study (2009–2014) in ICU patients with confirmed A(H1N1)pdm09 infection. We assessed the potential of biomarkers and clinical variables upon admission to the ICU for coinfection diagnosis using CHAID analysis. Performance of cut-off points obtained was determined on the basis of the binominal distributions of the true (+) and true (−) results. Results: Of the 972 patients included, 196 (20.3%) had coinfection. Procalcitonin (PCT; ng/mL 2.4 vs. 0.5, p < 0.001), but not C-reactive protein (CRP; mg/dL 25 vs. 38.5; p = 0.62) was higher in patients with coinfection. In CHAID analyses, PCT was the most important variable for coinfection. PCT <0.29 ng/mL showed high sensitivity (Se = 88.2%), low Sp (33.2%) and high negative predictive value (NPV = 91.9%). The absence of shock improved classification capacity. Thus, for PCT <0.29 ng/mL, the Se was 84%, the Sp 43% and an NPV of 94% with a post-test probability of coinfection of only 6%. Conclusion: PCT has a high negative predictive value (94%) and lower PCT levels seems to be a good tool for excluding coinfection, particularly for patients without shock. Highlights: CHAID model illustrates multilevel interactions among risk factors to identify stepwise pathways for detecting bacterial coinfection. PCT was the strongest variable associated with coinfection diagnosis by CHAID model analysis. Low serum levels of PCT (<0.29 ng/mL) in patients without shock were an accurate predictor for ruling out coinfection. PCT was a more accurate marker than CRP for coinfection diagnosis.